BIMBINGAN TEKNIK (BIMTEK) BAGI MAHASISWA TENTANG TEKNIK RELOKASI TELUR PENYU DI GAMPONG KEUDE PANGA KECAMATAN PANGA KABUPATEN ACEH JAYA - Mohamad Gazali (Jurnal Marine Kreatif, 2018)
Sea turtle undertaken a process of egg laying in once that yield almost hundreds eggs. Meanwhile, the eggs can be alive only several eggs. According to IUCN (International Union Conservation of Nature and Natural Reserve) in 1963 stated that such condition that caused a number of population is decreased. The target of community that involved in the technical guidance regarding egg sea turtle relocation namely undergraduate student of fisheries and marine science faculty, University of Teuku Umar. According to survey and interview that coastal community still undertook to hunting sea turtle’s eggs for trading in the traditional market dan restaurants. The priority problem that face in coastal community dinamic especially Panga Pasie area. for instance, eggs hunting that caused economical problem in order to can be survive in life. In other hand, the exploitation action cause reducing sea turtle population drastically in nature. Thus, if nobody care to effort of sea turtle conservation that undertook by stakeholder so, it occured a scarcity of sea turrtle that already enter in redlist IUCN category. It is caused  disturbance of environment and marine biodiversity in balance a marine ecology. The technical guidance including survey of nesting site, sosialization of sea turtle properties, focus group discussion (FGD) and tecnique of sea turtle eggs relocation. Overall activity of community serving that undergo on time and get a supporting from udergraduate student.